Problems with Adaptation of Post-Accession Polish Migrants in Countries of the EU - Hab Czop Edyta (European Scientific Journal, ESJ, 2017)
Starting from 1st May, 2004 countries of European Fifteen have gradually opened their labour markets for the new EU members, including the Poles. The first to take this step was Great Britain, Ireland and Sweden, the last - Germany and Austria. For the new EU citizens, emerging opportunities were connected with benefits and wide possibilities, but also with limitations and adaptation difficulties. They had to deal with the language barrier as much as the different culture, accepted behaviours, traditions, work culture and model of spending leisure time. Mentality of migrants – whether they were able or not to immerse into the “new” – had impact on finding themselves in another environment. Most of those, who left Poland did not plan to settle, they were leaving “for some time”, temporarily. Mentally, they were still connected with previous place of residence, more interested in environment left behind than new one. Such behaviour was not conducive to adaptation; on the contrary, it made adaptation harder. Migrants through listening to Polish radio, watching Polish television stations, using the Polish Internet portals and reading national press, separated themselves from the new environment. All of these was due to the assumption that engaging in new place has no point since their stay is only temporary. Their attitude to the kind of work and workplace was similar. Majority of migrants from the EU-8 countries was taking up secondary employment, regardless of educational background. Wages comparable with Polish were supposed to compensate depreciation on the labour market. A wide spectrum of adaptation problems of Polish migrants is an issue raised in reports prepared by specialized research institutions, the Polish Ministry of Foreign Affairs and Polish Community organisations.